Genotyping of Eusideroxylon zwageri Teijsm & Binn. and Potoxylon melangangai Kosterm. (Borneo Ironwood) using damd markers - Choo, Mee Yoon. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Borneo Ironwood or Belian is the endemic hardwood timber in Borneo and Sumatra. There are two species of Bel ian, i.e. Eusideroxylon zwageri and Potoxyloll melagangai. Both species arc difficult to distinguish because ofsimilar morphological characteristics. The detection and analysis ofONA polymorphisms in Belian is an essential component for species identification. The genotyping ofBelian was carried using Direct Amplification Minisatellite DNA by peR (DAMO-PCR) with two minisatellite primers: primer 33.6 (5'-AGGGCTGGAGG-3 ') and primer YNZ-22 (5'-CfCTGGGTGTGGTGC-3 '). The optimum annealing temperatures for each species was optimized, i.e. E. zwageri (47.6°C) and P. melagangai (50.00C) from primer 33.6; E. zwager; (56.0°C) and P. melagangai (51.4°C) from primer YNZ-22. The products of DAMD-PCR from both species of Belian showed a high degree of polymorphism. A total of five distinct diagnostic bands were successfully identified of each primer. However, only two of the diagnostic bands ofeach primer were excised and purified. i.e. 33.6 ZOI and 33.6 Z02 from E. zwageri; YNZ MOl and YNZ M02 from P. melagangai. All these purified PCR products were sent for DNA sequencing. However, the sequencing results were in weak signal due to the poor quality and impurities of DNA.